LESSONS LEARNED AND GOOD PRACTICES FORTHE FORMULATION AND IMPLEMENTATION OF APSYCHOMOTOR PROJECT FOR CHILDREN - Villalobos-Víquez, Grettel (2025)
The present investigation, part of the study of cases as a methodology, with the purpose of determining key aspects in the success of the management of the project “Children’s Psychomotricity” of the National University. The framework of the issue and conceptual references that allow contextualizing the project are constituted. Next, the application of the nine areas of project management established by the Project Management Institute is explained and evidenced: integration, scope, time, costs, quality, human resources, communication, risks and acquisitions in the project. As a result, the investigation concluded that the project manages the aforementioned areas in a timely manner, thus achieving the objective of the project, and turning it into a benchmark of good practices and lessons learned from the formulation and execution, so that other projects of social character such as “Children’s Psychomotricity” can be developed effectively in other locations.